The Ten commandments - DeMille, Cecil B. 1881-1959. (Cecil Blount).; Paramount Pictures Corporation ([Calif.] Paramount, 1956)
The story of the life of Moses, once favored in the Pharaoh's household, who turned his back on a privileged life to lead his people to freedom.
Part 1 (1 hr., 55 min.) -- part 2 (1 hr., 53 min.)
This work was compiled from many sources and contains material from the books, The Prince of Egypt by Dorothy Clarke Wilson, Pillar of fire by J. M. Ingraham, On eagle's wings by A. E. Southon.
VHS.
Produced and directed by Cecil B. DeMille ; written for the screen by Aeneas Mackenzie, Jesse L. Lasky Jr., Jack Gariss, Fredric M. Frank.
Charlton Heston, Yul Brynner, Anne Baxter, Edward G. Robinson.
Keywords: Moses -- (Biblical leader) -- Feature films; Religious films